ANALISIS FUNGSI KOMUNIKASI SECARA INFORMATIF, REGULATIF, PERSUASIF DAN INTEGRATIF DENGAN PELAYANAN INFORMASI DI KANTOR SEKRETARIAT PD IBI PROVINSI BANTEN - ESAKA PRATALA (iLearning Journal Center, 2018)
One of the functions of the Banten Province Indonesia Midwives Association Secretariat is to provide information services to the Executive Branches and Executive Branches as well as stakeholders that include the private sector, educational institutions, and local governments, where the purpose of this study is to clearly understand the relationship between communication functions informative, regulative, persuasive and integrated with information services organized by the Banten Province Regional Council Secretariat. The results of the analysis that the communication function is informative, regulative, persuasive and integrative has a relationship with the ministry of information, where the relationship with the communication function can provide information services where the highest value of communication functions related to information services is the integrative communication function. In addition, the improvement of information services can be predicted, therefore the performance of the Banten Province Indonesian Midwives Association Secretariat's performance must be optimized if information services for all midwife members through the Executive Branch and Executive Branch become enhanced through the use of communication media that can be accessed quickly and accurately. Keywords : communication, integrative, informative, information services, regulatory